Designing a Virtual Environment to Evaluate Multimodal Sensors for Assisting the Visually Impaired - Khoo, Wai L.; Seidel, Eric L.; Zhu, Zhigang (Computers Helping People with Special Needs, 2012)
We describe how to design a virtual environment using Microsoft Robotics Developer Studio in order to evaluate multimodal sensors for assisting visually impaired people in daily tasks such as navigation and orientation. The work focuses on the design of the interfaces of sensors and stimulators in the virtual environment for future subject experimentation. We discuss what type of sensors we have simulated and define some non-classical interfaces to interact with the environment and get feedback from it. We also present preliminary results for feasibility by showing experimental results on volunteer test subjects, concluding with a discussion of potential future directions.